Haemonchus contortus infection of goats and the use of anthelmintic natural alternative : An updated review - Soliman, SM; Salem, HM; El-Saadony, M; Ahmed, AE; Saad, A; El-Saadony, MT (Journal of the Hellenic Veterinary Medical Society, 2024)
Haemonchus contortus is a gastrointestinal nematode common in small ruminants and is a significant cause of economic loss in livestock enterprises. Progressive anthelmintic resistance of Haemonchus contortus is the most limiting factor in the effective control of this parasite. The utilization of botanical supplements with suspected anthelmintic activity for treating Haemonchus contortus is gaining popularity. This review aims to light on the prevalence of Haemonchus contortus in goats and possible control strategies to overcome such problems by using Allium sativum, commonly known as garlic, which has multiple health benefits.